The Protective Effects of Cath-MH With Anti-Propionibacterium Acnes and Anti-Inflammation Functions on Acne Vulgaris - Wu, Jiena; Guo, Ruiyin; Chai, Jinwei; Xiong, Weichen; Tian, Maolin; Lu, Wancheng; Xu, Xueqing (Frontiers in Pharmacology, 2021)
Acne vulgaris is a common adolescent skin condition which is mainly caused by Propionibacterium acnes overcolonization and subsequent inflammation. Our previous studies have demonstrated that Cath-MH, an antimicrobial peptide from the skin of the frog Microhyla heymonsivogt, possesses potential antimicrobial, LPS-binding, and anti-septicemic properties. However, its protective effects and potential mechanisms against acne vulgaris are still unclear. In the present study, its anti-P. acnes effects were measured by two-fold broth dilution method, agglutination assay, scanning electron microscopy and confocal laser scanning microscopy experiments. Its treatment potential for acne vulgaris was further evaluated in mice ear inoculated by P. acnes. In addition, the binding ability between Cath-MH and LTA was measured by the Circular Dichroism and antibacterial assay. Moreover, the anti-inflammatory efficiency of Cath-MH was evaluated in LTA- and LPS-induced RAW 264.7 macrophage cells. Cath-MH was found to kill P. acnes with a MIC value of about 1.56 μM by membrane disruption mechanism. It also exhibited agglutination activity against P. acnes. Cath-MH was able to bind LTA as well as LPS, inhibit LTA/LPS-stimulated TLR2/4 expression, and subsequently decreased the inflammatory response in RAW 264.7 cells. As expected, Cath-MH alleviated the formation of edema and the infiltration of inflammatory cells in acne mouse model with concurrent suppression of P. acnes growth and inflammatory cytokines expression in vivo. The potent P. acnes inhibition activity combined with powerful anti-inflammatory effect of Cath-MH indicates its potential as a novel therapeutic option for acne vulgaris.